2012
DOI: 10.1007/s13205-012-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted sex differentiation in date palm using simple sequence repeats

Abstract: Microsatellite markers containing simple sequence repeats (SSRs) are a valuable tool for genetic analysis. Our objective was to identify microsatellite markers that could be used to differentiate between male and female date palm (Phoenix dactylifera). The date palm is a dioecious plant whose sex cannot be determined until it reaches a reproductive age between 5 and 10 years. An early selection and/or differentiation of young seedlings into males and females could enhance breeding and assist research programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
3
23
1
1
Order By: Relevance
“…Additionally, Younis et al (2008) also reported five different male-specific amplification (of about 340, 1010, 375, 590 and 920 bp long) using five different ISSR primers. Another attempt was made to identify sex-specific microsatellite markers from date palm and 14 simple sequence repeat (SSR) primer pairs were used to screen 34 cultivars of date palm (Elmeer and Mattat 2012). Out of 254 numbers of detected microsatellite loci, 22 were found to identify 75% male samples of date palm.…”
Section: Date Palm (Phoenix Dactylifera L)mentioning
confidence: 99%
“…Additionally, Younis et al (2008) also reported five different male-specific amplification (of about 340, 1010, 375, 590 and 920 bp long) using five different ISSR primers. Another attempt was made to identify sex-specific microsatellite markers from date palm and 14 simple sequence repeat (SSR) primer pairs were used to screen 34 cultivars of date palm (Elmeer and Mattat 2012). Out of 254 numbers of detected microsatellite loci, 22 were found to identify 75% male samples of date palm.…”
Section: Date Palm (Phoenix Dactylifera L)mentioning
confidence: 99%
“…Several of these markers have been extensively used to study the genetic variation of date palm cultivars. These include randomly amplifi ed polymorphic DNA (RAPD), amplifi ed fragment length polymorphism (AFLP), and microsatellite markers (SSRs) (Ahmed et al 2013 ;Elmeer and Mattat 2012 ;Fig. 2.4 ).…”
Section: Fig 23mentioning
confidence: 99%
“…Nevertheless, dioecy may have evolved several times in plants from bisexual (hermaphroditic or monoecious) ancestors by (1) a fi rst mutation causing male sterility generating a gynodioecious population and (2) a second mutation resulting in a decreased female fertility in the population leading to functional dioecy (Cherif et al 2012 ). Whether the evolution of dioecy results from selection for outcrossing or from sexual selection on separate components of male and female fi tness has been a subjected of considerable debate (Elmeer and Mattat 2012 ;Weiblen et al 2000 ). However, there is strong evidence suggesting that dioecy appears to have evolved most frequently via monoecy, perhaps through divergent adjustments of fl oral sex ratios between individual plants (Weiblen et al 2000 ).…”
Section: Genetics and Breeding Systemmentioning
confidence: 99%
“…It is more practicable to make a selection in the nursery of healthy females, along with a few healthy males, to establish a seedling-date plantation. Current molecular studies (Aberlenc-Bertossi, et al, 2010;Ageez and Madboly, 2011;Bekheet and Hanafy, 2011;Cherif et al, 2012;Elmeer and Mattat, 2012;Moghaieb et al, 2010;Younis et al, 2008) are expected to provide the means to identify the gender of seedlings at an early stage and thereby simplify propagation and breeding. Early selection of young seedlings could enhance date palm breeding programs and generate experimental male and female genetic stocks (Siljak-Yakovlev et al, 1996).…”
Section: Seedling Date Palm Propagationmentioning
confidence: 99%
“…Early selection of young seedlings could enhance date palm breeding programs and generate experimental male and female genetic stocks (Siljak-Yakovlev et al, 1996). Molecular markers would facilitate the identification and selection of good male pollinators for use in breeding programs and could be used to select date palm with desired traits such as high yield and improved physical and chemical fruit characteristics (Elmeer and Mattat, 2012).…”
Section: Seedling Date Palm Propagationmentioning
confidence: 99%